Isolation and characterization of probiotics bacteria from curd, pickle and fermented rice and screening of antimicrobial activity - Acharya, Prangya Paramita; Sahu, Ajay Kumar; Kar, Barsha Barsha; Meher, Soumya Ranjan; B, Dr.Kirankumar (Asian Journal of Pharmaceutical Research and Development, 2019)
The live supplement of microorganisms though the dietary product is known as the probiotics. These are some special kind of bacteria they are healthy for the host organisms. These bacteria commonly found in food and dietary product. In our study, probiotics were isolated from fermented rice, curd and pickle .Total isolated strains were studied for their characterization, and also strains were studied antibacterial also their antibiotic susceptibility quality. The antibiotic resistance of potential strain was studied using Vancomycin, gentamycin, chloromphenicol, ciprofloxacin and cefataximide. PB1, PB3 shows the good resistance activity to the antibiotics. The curd produced by those strains has good quality and quantity of nutrients. Specially this study is for isolating, identifying, and characterizing the probiotics .Isolated strains were identified by Gram staining, catalase assay, and 3 molecular identification methods; namely, (GTG) 5-PCR fingerprinting, This experiments shows the better anti-pathogen activity, and acceptable antibiotic susceptibility; it implies we can use these probiotics in different purpose in food industry for modern food synthesis, for antimicrobial susceptibility test we are taking amplicin, karamycin, tetracycline, tripsin by using of the antibiotics concluded that various inhibition zones of given sample of probiotics.